Friend or fiend? - Blume, Judy; Pankhurst, Kate (Macmillan Children's London, 2008)
It's Fluzzy's birthday, and Jake (the pain) and Abigail (the great one) want to throw him the best party ever. But it's not long before they start arguing, and it takes a seriously sticky ice cream incident for them to make up. Suggested level: primary